Indeksikalitas Makanan Tradisional dalam Upacara Pawiwahan Masyarakat Desa Tibuneneng - Ni Nyoman Widani; Nelsye Lumanauw; Wiya Suktiningsih (LPPM Universitas Bumigora Mataram, 2021)
Traditional ceremonies are part of the culture and traditions of the Tibubeneng village community and are also related to the activities of the Hinduism. In the implementation of customs there are rules and prerequisites that must exist, one of which is traditional food. This study aims to find out the function and existence of a food in the traditional ceremony of the Tibubeneng tourism village community. The research method used in this research is descriptive qualitative research method. The ethnographic method is used by researchers to analyze the function and meaning of traditional foods used in traditional ceremonies, judging from the current form of performance whether there is a difference with a requirement in the rules of a traditional ceremony. To analyze activities, activities, meaning of traditional food used in traditional ceremonies, researchers will conduct in-depth interviews with the Bendesa adat, Pemangku adat and Stakeholders. There are 8 types of food that must be present in the Pawiwahan event, namely: Sambal embe, satay, lawar, Jukut, tum, urab, be'urutan, betutu. Every food that must be served as the main staple food in the Pawiwahan ceremony has meaning and is believed to be a category. prayer for the bride and groom when entering domestic life. These foods are also categorized as sacred/holy foods, because they are used as offerings/bantens in religious ceremonies or customs of the Balinese ethnic community. Along with the rate of population growth in Tibubeneng Village, many immigrants from various ethnicities and religions settled in Tibubeneng village, influencing the original culinary culture of the Tibubeneng village community. However, the strong application of awig-awig by the surrounding community is able to maintain the indexicality of traditional foods that must be present in the Pawiwahan ceremony.